Meatballs and Nuggets Production Training for Women's Entrepreneurial Group in Bobaneigo Madihutu Village, West Halmahera District - Yusnaini, Yusnaini; Rusliana, Erna; Saleh, Muhamad; Sapsuha, Yusri (Agrikan Jurnal Agribisnis Perikanan, 2023)
The chicken meat processing training was conducted in the women entrepreneurs group in Bangko, Bobaneigo Madihutu District, West Halmahera Regency, which was a community service activity focusing on the development of processed chicken meat products by utilizing the natural resources in Bangko, namely cassava. The aim of this community service was to improve the skills of the group members and to diversify the partner products that use cassava flour in processed chicken meat products such as chicken meatballs and chicken nuggets. These products can be used as additionally potential sales products for the partners because there were no meatball and nugget sellers in the area. To achieve the objective, socialization, training, and discussions with partner groups were conducted. The discussion was conducted with the aim to discuss the planning for implementation of the activities, product development, and continuity of activities by selling products from the service activities, which could increase the income of the women entrepreneurs group.